KECENDERUNGAN DAN TIPIKAL DISRUPTIVE BEHAVIOR DALAM SITUASI PEMBELAJARAN - annur - aliyyu; nani m sugandhi; Ilfiandra - - (Edusentris, 2022)
AbstractFacing disruptive behavior is the struggle of every teacher in learning. The teacher will spend a lot of time disciplining students before starting learning. Disruptive behavior that is carried out continuously without appropriate intervention has the potential to disrupt teacher performance and student learning success. The purpose of this study is to describe the tendencies and typical disruptive behavior in learning situations. The study uses a quantitative approach with descriptive methods. The instrument used was a Disruptive Behavior Scale questionnaire adapted from the Disruptive Behavior Scale Professed by Students (DBS-PS) instrument developed by Feliciano H Veiga from Universidade de Lisboa, Portugal. The population and sample of the study were 115 students of Class X of SMA Negeri 2 Sukabumi City. Data on trends and typical disruptive behavior use descriptive statistical procedures. The results showed that the general disruptive behavior of students was in the category of being headed low. Typical disruptive behavior of students is included in the category of distractions (distraction transgression) associated with disturbances, neglect, and violations of the rules. Research recommendations are aimed at teacher guidance and counseling.